Implementasi Pembelajaran Sains dalam Kurikulum Merdeka: Membangun Kemandirian Berpikir Siswa Sekolah Dasar - Waseso, Hendri Purbo; Sekarinasih, Anggitiyas; Prasetyo, Sigit (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to examine the effectiveness of science learning within the framework of the Independent Curriculum in elementary schools, focusing specifically on how this curriculum supports the development of critical, analytical, and collaborative thinking skills in students.Method – This research employs a qualitative approach with content analysis methods, using the official document from the Educational Standards, Curriculum, and Assessment Agency (BSKAP) No. 008/H/KR/2022 as the main data source. Data collection involved documentation studies, observations, and interviews, while analysis was conducted through thematic-content analysis, including data reading, coding, theme arrangement, and report generation.Findings – The findings suggest that the phased curriculum structure (Phases A, B, and C) facilitates personalized learning, allowing students to progress at their own pace. The integration of science and social studies in IPAS promotes a holistic approach, focusing on inquiry-based learning, knowledge application, and systemic concepts of nature-society interaction. The curriculum enhances cognitive, affective, and psychomotor skills while fostering critical and practical thinking. The Independent Curriculum increases the relevance and engagement of science learning, strengthening students' knowledge and critical thinking skills. Research Implications – This research highlights the need for further examination of the curriculum's long-term impacts on student achievement and suggests additional strategies for optimizing its implementation in various educational contexts.